Al cuidado del cuerpo del Rey: Los sumilleres de corps en el siglo XVIII - Gómez-centurión Jiménez, Carlos (Cuadernos de Historia Moderna, 2003)
Head of the Privy Chamber of the sovereign, the sumiller de corps –or Grand Chamberlainhad been from the end of the Middle Ages one of the most coveted posts of the Royal Household, because it brought the office-holder into daily contact with the king, and thus enabled him to become the principal beneficiary of royal friendship and favours. Despite its relevance, this office –like the other titular headships of the Spanish Royal Householdis in need of monographic studies and prosopographical analysis. This article explores the institutional evolution of the office, and offers a social profile of its holders during the XVIII century.